Seamanship techniques shipboard and marine operations - House, D. J. (Routledge, Taylor & Francis Group, 2019)
Ideal for Merchant Navy Officers from Cadet rank to Master Mariner, the fifth edition ... has been updated to include more information on topics as diverse as electronic navigation and AIS technology whilst still including essential information on subjects such as safety at sea, rescue operations, watch keeping duties and pollution control. Used by training establishments around the world, this best seller is the only reference to both shipboard practice and ship operations that seafarers will need.